Development of Augmented Reality (Ar)-Based Interactive Digital Magazine Media for Class X Chemistry Bond Learning - Sri A. Sari; Febby F. Damanik (Universitas Tadulako, 2025)
Technological advancements demand innovation in learning media, particularly in the digital era. Chemistry lessons, such as those on chemical bonds, are often considered abstract and difficult for students to grasp. Therefore, engaging, interactive, and contextual learning media are needed. The use of interactive digital magazines based on Augmented Reality (AR) is expected to enhance conceptual understanding and student learning interest. The study successfully developed and tested an AR-based interactive digital magazine for teaching atomic bonding to Grade X learners, yielding highly positive results in terms of validity, effectiveness, and user satisfaction. The media achieved a validity score of 95.1% for material and 95% for media aspects, with an N-Gain score of 0.7964 indicating high effectiveness. Additionally, teacher practicality was rated at 93.74%, and learner responses reached 89.75%, both rated as very high, confirming the media's feasibility and effectiveness for studying atomic bonding concepts.